Rapid liver graft implantation in canine: A preliminary study - Jie Hao; Jia-Wei Yu; Jing-Wen Xiao; Lin-Biao Xiang; Rong Peng; Jia-Qi Quan; Ya-Xu Dong; En-Hui Li; Juan-Juan Wang; Lu Ren; Yong Wan; Hong-Ke Zhang; et al. (Surgery Open Science)
Background: The current method for liver graft implantation during the anhepatic phase is complex. Therefore, this study aimed to introduce a modified orthotopic liver transplantation (OLT) technique with major vascular reconstruction using cuff technique to simplify the process of liver graft implantation during the anhepatic phase. Methods: Twenty-four canines were randomly assigned to two groups: the modified orthotopic liver transplantation group (M-OLT, n = 12) and the control group (n = 12). All animals were randomly assigned to the donor or recipient groups. The recipients received orthotopic liver transplantation using a modified technique in the M-OLT group, and OLT using traditional implantation technique without venovenous bypass was performed in the control group. The donor and recipient characteristics were compared between the two groups. Vascular anastomotic patency was evaluated using angiography immediately and one week after surgery. Results: All recipients underwent successful liver transplantation. There were no significant differences between the two groups in terms of sex, body weight, or cold ischemia time of the donor liver. However, recipients in the M-OLT group had a shorter operation time, less intraoperative blood loss, shorter anhepatic phase, shorter vascular occlusion time, and shorter warm ischemia time than that in the control group (all p < 0.05). No anastomotic leakage or stenosis was detected in either group after liver transplantation. One recipient in the M-OLT group and three in the control group died within one week of transplantation. Conclusions: This modified technique is safe and feasible for canine liver transplantation and can significantly simplify liver graft implantation procedures during the anhepatic period.